The pricing framework agreements in the Colombian government contracting does a possible monopoly and favoring large industries? (2014)
This essay aims to analyze the possible monopoly pricing framework agreements between large industries and Colombian State hiring. The Law 1150 of 2007 should be taken as reference whereby the national government bylaw pricing framework agreements for the acquisition of goods and services of uniform technical characteristics and common use, Decree Law 4170 of 2011 by which it was created the National Agency for Public Procurement, Colombia Purchase Efficient, entity in charge of designing, organizing and conducting the pricing framework agreements and Decree 1510 of 2013 which states the application of pricing framework agreements in the State Entities.